Desarrollo de un microencapsulado del extracto de chillangua (Eryngium foetidum), mediante secado por aspersión. - Navarrete Cruz, Lenin Vladimir (2022)
The present research work was made with the purpose of microencapsulating the “chillangua” plant extract, by means the spray drying. Therefore, it was dehydrated the plant in an oven for 24 hours at 40 °C, the bioactive compounds were got, through a crude drug maceration with ethanol (99,8%), by means of the rotary evaporator was eliminated the solvent to get the extract aqueous, which it was got a pH of 5.70, 1,65 °Brix total solids, 98,42 % humidity, 1,085 g/cm^3 density and an antioxidant 1895,30 µmolFe+/g capacity sample. With the Design Expert 8.0.6 software, it was established a 13 experimental runs response surface mathematical model. For the spray drying process, it was taken the feed flow rate independent variables of (VFA) 500, 600 and 700%, and the (TAE) 130, 140 and 150 °C inlet air temperature. The best conditions for microencapsulation are 149,93 mL/h VFA and 500,20 °C, where it was got a 92,9901% yield, 2,1095% humidity, 90,8001% microencapsulation efficiency in the experimental part. The characterization of chillangua optimized microencapsulation, presented a light greenish golden yellow color, menthol aroma, mild flavor, homogeneous particles, 21,99% hygroscopicity, apparent density 5,701 g/ml, compacted density 5,65 g/ml, pH of 5,5, repose 36° angle, solubility 93%, Hausner index 5,65 %, Carr index 49%, iron reducing antioxidant capacity 903,99 (µMFe2+/g) and the morphology 26,24µM.